PENGARUH IMBALAN, LINGKUNGAN KERJA, TERHADAP KINERJA PEGAWAI DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA APARTEMEN BOTANICA JAKARTA - Guston Sitorus (Jurnal Manajemen, 2019)
The objective of this research is to anlize and test the effect of rewards, work enviroment, and job satisfaction on performance. Performance is assumed to be significantly effected by the rewards, work enviroment, and job satisfaction that pertain in the organization. The causal study reported here aimed to examine the hypothesis. It was conducted through a survey in the Apartemen Botanica Jakarta a sample of 111 people randomly selected from the overall population of 135 employe. The data of each variable were collected separately by the respondens’ filling in a questionnaire. The path technique was applied to analyze the data wich had been previously treated with the aggressive and coorelation procedure. The result proved that the employee performance was directly effected by the rewards, the work envoroment and job satisfaction was in turn, directly effected by rewards and work enviroment. The findings suggest that the variation of performance of the employee might have been effected by the rewards, the work enviroment, and the job satisfaction in the organization. This further implies the need take the variables of rewards, job satisfaction, and performance into the consideration in the strategic planning of the human resources development in the Apartemen Botanica Jakarta